PRINCIPALS’ BUDGET MANAGEMENT PRACTICES AND SECONDARY SCHOOL PERFORMANCE IN OYO STATE, NIGERIA - OYENIRAN, SAHEED; ADEBAYO, MUSTAPHA AFEEZ; OSASONA, FAITH OLAYINKA; TUMBURKU, WAKKALA GARBA (Sokoto Educational Review, 2025)
This article examined principals' budget management practices and secondary school performance in Oyo State, Nigeria. A quantitative research approach was employed, with 599 of the 605 selected respondents participating in the study. Data was collected using three questionnaires. Descriptive statistics (mean scores and standard deviation) were used to answer the three research questions. One main hypothesis and four operational hypotheses were tested using Pearson Product-Moment Correlation at a 0.05 significance level. The study found that: (1) planning, monitoring, controlling, and budget record-keeping are the budget management practices employed by secondary school principals in Oyo State; (2) the level of secondary school performance in Oyo State was high; and (3) a significant relationship existed between principals' budget management practices and secondary school performance (p-value = 0.034 < 0.05). The study concluded that principals' budget management practices, as well as the participation of account officers in school budget management, play a significant role in secondary school performance in Oyo State. Among the recommendations, the study suggested that the Oyo State government should involve school principals and teachers in budget management practices, including planning and implementation. DOI: https://doie.org/10.0303/SER.2025355470